Les professions intermédiaires des entreprises en butte à d’importantes transformations et tensions au travail - Jean-Paul Cadet; Patrick Conjard; Anne Gillet; Christophe Guitton (Cahiers de la Recherche sur l'Education et les Savoirs)
It is important to analyze the changes in work that characterize the intermediate professions of the enterprises (supervisors, technicians, intermediate administrative and commercial professions), with a view to adjusting the formations that are supposed to lead to these professions, such as the DUT. In support of collective research on the status and dynamics of these occupations, three main trends are highlighted: a development of versatility; a submission to various processes of rationalization (prescription, standardization, supervision and evaluation of work) as both objects and actresses; a confrontation with new tensions in the course of work, linked in particular to the two major trends mentioned above. These developments are primarily interpreted in the light of contemporary changes in corporate strategies, labor organizations and managerial practices.